SWOT Analysis Nomadic Tourism as Millennial Friendly Natural Tourist Destination Development Strategy (Case Study: Glamping De Loano, Purworejo) - Laksmi, Gratia Wirata; Rahmanita, Myrza; Brahmantyo, Himawan; Nurbaeti, Nurbaeti (Institut Pariwisata Trisakti, 2021)
The purpose of this study is to analyze the alternative strategy of developing local tourism around Borobudur, one of the world’s heritage as the top choice of foreign and domestic tourists, that focused on developing a variety of alternative tourism infrastructures while preserving the environment that is a millennial-friendly destination that is called Nomadic Tourism in Glamping De Loano, Purworejo, Indonesia. The research took place between June-July 2020 in Glamping De Loano, Purworejo. The chosen methods including documentation, observation, and interviews with local government groups, visitors, and residents. Glamping De Loano is a new and fresh tourism sensation in Purworejo that can bring millennial tourists and new unique tourism experiences to the area. It is a new early-stage of destination because it has only been operated for less than a year but has many opportunities that can be cultivated and developed. However, most complaints coming from them are regarding narrow and dangerous road infrastructure towards the destination, supporting ecosystem readiness, and conformity of the biophilic material to the environment surrounding. Most interviewers suggest it would be better with improved road infrastructure construction and focus on providing a basic supporting ecosystem. Recommendations are made for developing the Glamping De Loano tourism better to improve the experience of tourists and visitors and to improve the resident’s quality of life. It is hoped that this research may prompt local authorities to take l residents’ perceptions and experiences into account by creating better management measures and regulations. Keywords: Nomadic Tourism, Destination Development Strategy, Glamping, Purworejo, Borobudur